2017
DOI: 10.28991/cej-030937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Critical Success Factors in Urban Housing Projects Using Fuzzy Analytic Network Process

Abstract: Population growth and increasing trend towards urbanization have caused housing demand to exceed its supply, particularly in urban areas in developing countries. Furthermore, housing industry motivates many subsidiary industries and plays a leading socio-economic role in such countries. Therefore, successful completion of housing projects is of great significance quantitatively and qualitatively.This study aims to propose a framework to evaluate the critical success factors (CSFs) in housing projects consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Against this backdrop, urban regeneration has been highlighted as an effective means for settling these sustainability problems [4]. Through housing condition improvement and infrastructure updating, urban regeneration projects (URPs) can bring a new look to old urban centers and enhance urban residents' quality of life [5]. By reusing brownfields and re-planning existing urban areas, URPs contribute to environmental protection, carbon emission reduction, and land use optimization [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this backdrop, urban regeneration has been highlighted as an effective means for settling these sustainability problems [4]. Through housing condition improvement and infrastructure updating, urban regeneration projects (URPs) can bring a new look to old urban centers and enhance urban residents' quality of life [5]. By reusing brownfields and re-planning existing urban areas, URPs contribute to environmental protection, carbon emission reduction, and land use optimization [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…By reusing brownfields and re-planning existing urban areas, URPs contribute to environmental protection, carbon emission reduction, and land use optimization [6,7]. Additionally, URPs can promote real estate industry development and provide new job opportunities for local people, which spurs economic growth [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-six e-learning experts participated in this study. The sample size was sufficient to run the FANP analysis as per previous studies by (Bathaei et al, 2019 ; Hemmati et al, 2018 ; Nilashi et al, 2016 ; Sadeghi & Larimian, 2018 ; Youneszadeh et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…(1/10,1/9,1/8) size was sufficient to run the FANP analysis as per previous studies by (Bathaei et al, 2019;Hemmati et al, 2018;Nilashi et al, 2016;Sadeghi & Larimian, 2018;Youneszadeh et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It was concluded that financial organizations should make housing loan more accessible together with stable micro-economics in other to enable developers to deliver housing successfully. Youneszadeh et al, (2017) also adopted Fuzzy Analytic Network Process (FANP) for evaluating the CSFs in urban housing. The study adopted a three-step wise evaluation process; identifying the CSFs, redefining and categorizing CSFs using the Delphi method and finally ranking the CSFs using the fuzzy network process.…”
Section: Critical Success Factors For Sustainable Housingmentioning
confidence: 99%